Vegetation and Climate Around 780 Kyrs BP in Northern Kathmandu Valley, Central Nepal - Humagain, Sima; Paudayal, Khum N. (Bulletin of the Department of Geology, 2018)
Palynological study from the Dharmasthali Formation exposed in the northern part of Kathmandu valley revealed the composition of forest vegetation that were growing in middle Pleistocene (780 kyrs BP) in this area. In a total fifteen samples were collected from the 46 m exposed section for the palynological study. The profile can be divided into two zones on the basis of pollen assemblages. The lower part (DF-I) is dominated by Pteridophyte spores such as Lygodium, Polypodium, Cyathea and Pteris. The dominance of Pteridophytes indicate that the forest floor was moist and humid. The tree pollen consists of Abies, Pinus, Quercus, Podocarpus and Alnus. Other Gymnosperms such as Picea and Tsuga were represented by very low percentage. Poaceae and Cyperaceae show their strong presence indicating grassland and wetland conditions around the depositional basin. In the upper zone (DF-II) there is increase of Gymnosperms such as Picea and Abies. The subtropical Gymnosperm Podocarpus decreased while Tsuga completely became absent in this zone. Cold climate preferring trees such as Cedrus, Betula, Juglans and Ulmus appeared first time in this zone. The climate became even colder and drier in the upper part of the section. Near water plants such as Cyperaceae and Typha show their dominance in this zone. The plant assemblages from bottom part of the Dharmasthali Formation indicate warm climate condition which was becoming colder after 780 kyrs towards the top part of the sequence. Bulletin of Department of Geology, vol. 20-21, 2018, pp:37-48